The effect of the corporate governance on the financial performance of SMEs: the case of Jordanian companies (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This study aims to examine the relationship between corporate governance and financial performance in Jordanian small and medium enterprises (SMEs).The present study has approached its objectives by examining the data relating to (40) companies during a period of six years from (2013-2018), starting from the year following the year of issuing the corporate governance code for SMEs in Jordan by Jordanian government. The descriptive analytical approach was used utilizing the statistical analysis program (IBM SPSS 24) based on data extracted from the financial statements of the subject sample.The results of the present study show a relationship between the corporate governance and the financial performance of medium and small enterprises in Jordan, in addition to the absence of a relationship between the efficiency of the board of directors and the financial performance of these companies. There was also a relationship between the independence of the board of directors and financial performance and a relationship between the size of the board of directors and the financial performance of medium and small enterprises. This study suggests that the supervisory authorities could possibly issue a set of laws and legislations to compel companies to adopt the principles of governance and raise awareness of the importance of corporate governance in business prosperity.
Keywords: SMEs; Jordan; Corporate Governance; Financial Performance; board of directors